An optimal configuration for a battery and PEM fuel cell-based hybrid energy system using developed Krill herd optimization algorithm for locomotive application - Yingying Guo; Xiangdong Dai; Kittisak Jermsittiparsert; Navid Razmjooy (Energy Reports, 2020)
A new methodology has been proposed for optimal size selection of a hybrid energy system (HES) including lithium-ion battery and polymer electrolyte membrane (PEM) fuel cell to supply the driving force of a locomotive. The main purpose is to minimize the total cost of HES with different constraints including the capacity constraint of the battery and the fuel cell state-of-charge limit The optimization problem has been solved based on a new improved model of the Krill Herd (KH) algorithm, converged krill herd optimization algorithm (CKH). Simulation results are analyzed based on the average power demand, speed demand of the locomotive, and the locomotive slope. The results of the presented CKH algorithm have been compared with the standard KH and PSO algorithm and the results declared that the total cost for HES based on CKH has the minimum value such that the value for the CKH for 0%, 1%, and 2% slope are 3.15106, 3.56106, and 3.93106 toward KH with 3.47106, 4.01106, and 4.56106 and PSO with 3.74106, 4.27106, and 4.72106 HES, respectively.
Keywords: 330; Converged Krill herd optimization algorithm; Energy management optimization; Hybrid energy system; Lithium-ion battery; Locomotive; PEM fuel cell